Taxonomic notes on Aciotis (Melastomataceae) from the Brazilian Amazon: A new species and the updated distribution of Aciotis ferreirana, a rarely collected species - Silva, Diego Nunes Da; Demarchi, Layon Oreste; Fernandes, Géssica E. A.; Pastore, Mayara; Guimarães, Paulo José Fernandes (Phytotaxa, 2026)
Aciotis manauara is described here as a new species to the municipality of Manaus, the capital of the Brazilian state of Amazonas. It was discovered in the Adolpho Ducke Forest Reserve and a surrounding area, in a forested campinarana and baixio habitats. Aciotis manauara is compared to A. indecora, A. rubricaulis, and A. viscida, the morphologically most similar species. To highlight diagnostic characters, we provide line drawings, photographs of living specimens, and scanning electron microscopy images of the leaf blades and seeds of A. manauara. Based on current available data, its conservation status is preliminarily assessed as Critically Endangered (CR) according to IUCN guidelines and criteria. In addition, we present an identification key and photographs of living specimens for the species of Aciotis occurring in the Adolpho Ducke Forest Reserve. Lastly, we reviewed the geographic distribution of the poorly collected species Aciotis ferreirana, which is endemic to the Brazilian Amazon and occurs only in the states of Amazonas and Rondônia. Its occurrence in Mato Grosso should not be recognized.